2022
DOI: 10.3390/app12052724
|View full text |Cite
|
Sign up to set email alerts
|

A Direct-Current Triboelectric Nanogenerator Energy Harvesting System Based on Water Electrification for Self-Powered Electronics

Abstract: This study aimed to develop a simple but effective mechanical-to-electrical energy conversion for harvesting hydrokinetic energy based on triboelectric nanogenerator (TENG) technology. Here, a direct-current fluid-flow-based TENG is reported as a potential solution to solve the inconvenience of directly powering electronic devices where direct-current (DC) power is required. The falling of a water droplet (about 1.06 mL) from an elastomeric pipe can generate an open-circuit voltage of ~35 V, short-circuit curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…These modes include contact separation, [43][44][45][46] lateral sliding, [47][48][49] free-standing, 19,20,[50][51][52][53][54][55][56][57][58][59][60][61][62][63] and single electrode modes. 15,33,[64][65][66][67][68][69][70][71][72][73]…”
Section: Basic Mode Of Operation Of Liquid-solid Triboelectric Nanoge...mentioning
confidence: 99%
See 1 more Smart Citation
“…These modes include contact separation, [43][44][45][46] lateral sliding, [47][48][49] free-standing, 19,20,[50][51][52][53][54][55][56][57][58][59][60][61][62][63] and single electrode modes. 15,33,[64][65][66][67][68][69][70][71][72][73]…”
Section: Basic Mode Of Operation Of Liquid-solid Triboelectric Nanoge...mentioning
confidence: 99%
“…Compared to the other modes such as contact separation, lateral sliding, and free-standing modes, which generate electricity due two the electrostatic induction process between two electrodes, a single-electrode-based L-S TENG has several advantages. 15,33,[64][65][66][67][68][69][70][71][72][73] Lin et al demonstrated a water-TENG with a superhydrophobic PTFE surface, working in a single-electrode mode, that can convert the energy from flowing water and falling droplets (Figure6a ). 15 This device can generate a maximum voltage and current of 9.3 V and 17 μA, respectively, from a water droplet of about 30-μL.…”
Section: Single-electrode Modementioning
confidence: 99%
“…It can harvest energy from ocean waves with a maximum frequency of 75 Hz. A TENG is designed in [78] to harvest electrical energy from the kinetic energy of water. A drop of water falls from an elastomeric pipe and passes through an electrode that generates an open circuit voltage for energy harvesting.…”
Section: -9 Kwmentioning
confidence: 99%
“…Energy harvesting using solar cells[57]-[61], AUV motion or kinetic energy[62]-[78] and marine life[79]-[90]. The symbol x indicates unspecified metric value.…”
mentioning
confidence: 99%
See 1 more Smart Citation